Target Compliance dalam Kebijakan Pembatasan Kegiatan Masyarakat (PKM) di Pasar Karangayu Kota Semarang sebagai Upaya Penanganan COVID-19 - Tuhfah Almasati,; Retno Sunu Astuti; Yuliana Kristanto (Journal of Public Policy and Management Review, 2021)
The COVID-19 pandemic needs to be overcome with the government's firmness in reducing the number of cases and reducing the expansion of the impact. Semarang in handling this outbreak implement the Restrictions on Community Activities through Semarang Mayor Regulation Number 28 of 2020. This policy limits people's activities outside the home, including in traditional markets. Close interactions between traders and buyers in traditional markets makes the transmission of COVID-19 cannot be avoided. A poor compliance with health protocol makes traditional markets need special attention in this policy implementation. This research aims to determine the level of target compliance and to figure factors that affect the target compliance with Semarang Mayor Regulation Number 28 of 2020 in Karangayu market. This study used a descriptive research method with a qualitative approach. The result showed that both Karangayu market’s traders and buyers are quiet comply with the policy. Furthermore, through the analysis of target compliance factors suggested by Weaver, this study indicates six factors of target compliance such as (1) lack of information, (2) the absence of insentives and insufficient sanction, (3) problem of monitoring, (4) the ability to fulfill resources, (5) the lack of autonomy, and (6) attitude and beliefs.